2012
DOI: 10.1186/1471-2164-13-469
|View full text |Cite
|
Sign up to set email alerts
|

A high-density genetic map of Arachis duranensis, a diploid ancestor of cultivated peanut

Abstract: BackgroundCultivated peanut (Arachis hypogaea) is an allotetraploid species whose ancestral genomes are most likely derived from the A-genome species, A. duranensis, and the B-genome species, A. ipaensis. The very recent (several millennia) evolutionary origin of A. hypogaea has imposed a bottleneck for allelic and phenotypic diversity within the cultigen. However, wild diploid relatives are a rich source of alleles that could be used for crop improvement and their simpler genomes can be more easily analyzed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 57 publications
2
74
0
Order By: Relevance
“…Placement was arbitrary within blocks with the same centiMorgan value. Scaffold orientation and placement were refined according to the conventional maps using, in order of priority, the tetraploid AB-genome map, the diploid F 2 A-genome Nagy map 22 (for the A. duranensis assembly), the diploid B-genome map 24 (for the A. ipaensis assembly) (Supplementary Data Set 2) and finally the tetraploid AB-genome Shirasawa map 17 . Markers were located on the scaffolds using BLAST and ePCR (electronic PCR) with high similarity parameters (taking the top hits only, with placement by BLAST (e value < 1 × 10 −10 ) given preference over ePCR where both were available).…”
Section: Genetic Maps Generated From Genotyping-by-sequencing Data Fomentioning
confidence: 99%
“…Placement was arbitrary within blocks with the same centiMorgan value. Scaffold orientation and placement were refined according to the conventional maps using, in order of priority, the tetraploid AB-genome map, the diploid F 2 A-genome Nagy map 22 (for the A. duranensis assembly), the diploid B-genome map 24 (for the A. ipaensis assembly) (Supplementary Data Set 2) and finally the tetraploid AB-genome Shirasawa map 17 . Markers were located on the scaffolds using BLAST and ePCR (electronic PCR) with high similarity parameters (taking the top hits only, with placement by BLAST (e value < 1 × 10 −10 ) given preference over ePCR where both were available).…”
Section: Genetic Maps Generated From Genotyping-by-sequencing Data Fomentioning
confidence: 99%
“…BeadChip (Akond et al, 2013) • SoySNP50K array (Song et al, 2013) • 384 SNP GoldenGate assay (Hyten et al, 2008 (Varshney et al, 2012a) • 292 lines • 20 (crossing parentals of recombinant inbred lines, introgression lines, MAGIC and NAM population; Kumar et al, 2016) • 60K Axiom®Cajanus SNP array (Saxena et al, 2017 and unpublished) (Gupta et al, 2017) • 35 (parental genotypes of mapping populations; Thudi et al, 2016a) • 129 released varieties (Thudi et al, 2016b) • 300 lines (ICRISAT, unpublished) • 3000 lines (ICRISAT, unpublished) • GoldenGate assays based on VeraCode technology (Roorkiwal et al, 2013) • 60K Axiom®Cicer SNP array (Roorkiwal et al, 2017 (Chen et al, 2016) • 11 genotypes including synthetics and their diploid parents (Chen et al, 2016) • 41 diverse genotypes (30 tetraploids and 11 diploids) (Clevenger et al, 2017;Pandey et al, 2017a) • 58K Axiom®Arachis SNP array (Pandey et al, 2017a) •1536 SNP GoldenGate assay (Nagy et al, 2012) Common bean • 80.57% of Phaseolus vulgaris var G19833 genome (587 Mb); 26 279 protein coding genes (Schmutz et al, 2014) • 17 varieties • BARCBean6K_1, BARCBean6K_2 chips, BARCBean6K_3 SNP chips (Song et al, 2013 (Deulvot et al, 2010) • Combines custom-made growth vessels and new image analysis algorithms to non-destructively monitor RSA development over space (2D) and time • Allows information on soil properties (e.g. moisture)…”
Section: High-density and Precise Phenotypingmentioning
confidence: 99%
“…Analyses of species outside section Arachis have been infrequent. Stalker (1985) reported that the two diploid section Erectoides species A. rigonii 3 A. paraguariensis hybrids had many univalents and Krapovickas and Gregory (1994) (Lu and Pickersgill, 1993;Stalker et al, 1994), seed storage proteins (Singh et al, 1991;Bianchi-Hall et al, 1993;Liang et al, 2006), Restriction Fragment Length Polymorphisms (RFLPs) Paik-Ro et al, 1992), Amplified Fragment Length Polymorphisms (AFLPs) (Milla-Lewis et al, 2005b); Simple Sequence Repeats (SSRs) (Hopkins et al, 1999;He et al, 2005;Hong et al, 2010;Guo et al, 2012;Nagy et al, 2012). Randomly Amplified Polymorphic DNA (RAPDS) (Halward et al, 1992;Lanham et al, 1992;Hilu and Stalker, 1995), and in situ hybridization (Raina and Mukai, 1999;Seijo et al, 2004).…”
Section: Cytology and Evolution Of Arachismentioning
confidence: 99%
“…However, they have had limited use in peanut due to the difficulties of their implementation in polyploid plants, and in Arachis it will require separation of A and B-genome sequences. A SNP-based map of diploid Arachis was developed by Nagy et al (2012) wherein a high-density genetic map of the A genome was developed from an intra-species cross within A. duranensis, and 598 SSRs, 37 single-stranded DNA conformation polymorphism (SSCP) markers, and 1,054 SNPs were mapped. SNP-based markers have not yet been extensively used on the tetraploid Arachis, but they are expected to greatly accelerate genetic mapping and marker-assisted selection when genotyping-by-sequencing (Elshire et al, 2011) can be routinely implemented.…”
Section: Introgressing Genes From Arachis Species To a Hypogaeamentioning
confidence: 99%